Default Agnosticism - Jonbäck, Francis (Religions, 2021)
Agnosticism has always had its fair amount of criticism. Religious believers often described the first agnostics as infidels and it is not uncommon to see them described as somewhat dull fence-sitters. Moreover, the undecided agnostic stance on belief in gods is often compared with being unsure about such obviously false statements as the existence of orbiting teapots, invisible dragons or even Santa Claus. In this paper, I maintain that agnosticism can properly be endorsed as a default stance. More precisely, I use a strategy presented by Alvin Plantinga and argue that it is rationally acceptable to be agnostic about the existence of God. I also anticipate and answer a number of objections. Finally, I offer my conclusion.